Phytophthora cactorum as a Pathogen Associated with Root Rot on Alfalfa (Medicago sativa) in China - Cai, Wenyong (Plant disease, 2020)
Alfalfa (Medicago sativa) is the largest grown pasture crop in China due to its economic and ecological importance. During the summer season from June to August in 2018, stunted plants was frequently observed in alfalfa fields that have been established for two years in Jinchang, Gansu Province. The disease incidence of root rot ranged from 40% to 50%. Taproots of stunted plants showed red-brown to dark brown discolorations, and lateral roots were poorly developed. Shoots wilted with rotted taproots and lateral roots in severely affected plants. Twenty symptomatic plants were collected and transported to the laboratory for pathogen isolations. Roots were washed under running tap water, cut into 2 to 3 mm pieces (40 pieces each plant), and then sterilized in 75% ethanol for 2 mins followed by three times washing with autoclaved distilled water. Surface dried pieces on autoclaved filter papers were put onto water agar and also a Phytophthora selective medium P5ARP(H) (Jeffers and Martin 1986). The plates were incubated at 22°C for 3 to 5 days and then the growing hypha were subcultured onto potato dextrose agar (PDA). Thirty-two Phytophthora-like isolates were obtained and showed similar morphologies on PDA. Five isolates picked randomly were purified by single-hyphal-tip and plugs (4 to 5 mm) from PDA cultures were incubated in petri dishes with autoclaved distilled water at 22°C for 5 days. Sporangia, chlamydospores and oospores were examined. Sporangia were usually ovoid and sometimes appeared ellipsoid, with the length of 30.5-39.1 μm and width of 23.4-27.8 μm. The diameter of chlamydospores was 29.6 to 42.5μm. Oospores had a diameter of 23.6 to 30.2 μm. The isolates were tentatively identified as P. cactorum based on these morphology characteristics (Montealegre et al. 2016). DNA of these isolates were extracted and PCR amplifications of the rDNA ITS region and cytochrome oxidase subunit I (Cox I) (Kroon et al. 2004) were conducted. Sequences of these isolates were then compared with reference sequences in GenBank using BLAST search. The 866-bp ITS sequences had a sequence identity of 99% to 100% with P. cactorum (e.g. accession nos. EU662221, KJ128036). In addition, the 663-bp CoxI sequences showed 100% sequence identity with three P. cactorum isolates (accession nos. AB688156, HQ708234, EU660851). The ITS and CoxI sequences of one representative isolate Phy.c2 have been deposited in GenBank with the accession no. MT280033 and MT344138, respectively. Pathogenicity of the five isolates (Phy.c1-Phy.c5) were determined on two-week-old alfalfa seedlings (cv. Longdong) grown from seeds. Inoculums were prepared by subculturing agar plugs from edges of PDA cultures into the flask with autoclaved millet seeds, and incubated at 22°C in darkness for two weeks and shaken by hand every two days to ensure uniform colonization. Seedlings were transplanted into pots (12 cm x 12 cm) filled with autoclaved potting mix infested with millet-seed inoculum of each isolate at a rate of 0.5% (w/w). Control seedlings for comparison were transplanted into pots with uninfested potting mix. There were five seedlings per pot and twelve replicate pots for both inoculated and noninoculated treatments, and pots were kept under controlled environment room (22°C, 12 h photoperiod and 65% relative humidity) that were watered every two days to free draining. 87%~92% of the inoculated plants showed stunted symptoms with poorly developed and brown-discoloured roots three weeks after inoculation while the control plants were healthy with no root disease symptoms. To fulfil Koch's postulates, re-isolated cultures from discoloured root tissues were confirmed as the inoculated isolates by morphological examination and ITS sequencing. The five-purified isolates were submitted to the Grassland Culture Collection Center, Lanzhou University, with the accession nos. LZU-MsR-Phy.c1-Phy.c5. To our knowledge, this is the first report of P. cactorum as a pathogen of root rot on alfalfa in China. Phytophthora spp. has been reported causing root rot on alfalfa in America, Australia and Canada, and other legumes such as chickpea, and many other crops worldwide (Musial et al. 2005; Tan and Tan 1986; Vandemark and Barker 2003), and P. cactorum was reported as a root rot pathogen on lavender in China (Chen et al. 2017). P. cactorum may be a significant pathogen associated with root rot in major commercial alfalfa-producing areas in China where are based on flood-irrigation during the growth season